Relative differential K-characters - Maghfoul, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We define a group of relative differential K-characters associated with a smooth map between two smooth compact manifolds. We show that this group fits into a short exact sequence as in the non-relative case. Some secondary geometric invariants are expressed in this theory.